The perfluoroadamantoxy aluminate as an ideal weakly coordinating anion? – synthesis and first applications. Issue 14 (16th March 2023) - Billion, Andreas; Schorpp, Marcel; Feser, Rebecca; Schmitt, Manuel; Eisele, Lea; Scherer, Harald; Sonoda, Takaaki; Kawa, Hajimu; Butschke, Burkhard; Krossing, Ingo
Abstract : Dream WCA…? The very high fluoride ion affinity of the Lewis acid underlying the novel WCA [Al(OC10 F15 )4 ] − ([ pfAd ] − ) nurtures the hope for having found a new "dream WCA". Yet, the paths towards this WCA held some obstacles at hand...! Abstract : Weakly coordinating anions (WCAs) facilitate the stabilization and isolation of highly reactive and almost "naked" cations. Alkoxyaluminate-based WCAs such as [Al(OC(CF3 )3 )4 ] − ([ pf ] − ) are widely used due to their synthetic accessibility and their high stability. However, small cations are still able to coordinate the oxygen atoms of the [ pf ] − anion or even to abstract an alkoxy ligand. The novel WCA [Al(OC10 F15 )4 ] − ([ pfAd ] − ; OC10 F15 = perfluoro-1-adamantoxy) is characterized by a very rigid core framework, thus indicating a higher stability towards fluoride-ion abstraction (DFT calculations) and providing hope to generate less disordered crystal structures. The [ pfAd ] − anion was generated by the reaction of the highly acidic alcohol perfluoro-1-adamantanol C10 F15 OH with LiAlH4 in o -DFB. Li[ pfAd ] could not be synthesized free of impurities (and still contains unreacted alcohol). Yet, starting from contaminated Li[ pfAd ], the very useful pure salts Ag[ pfAd ], [Ph3 C][ pfAd ] and [H(OEt2 )2 ][ pfAd ] could be synthesized. The salts were characterized by NMR spectroscopy, single-crystal X-ray diffraction and IR spectroscopy. Additionally, [NO][ pfAd ] could be synthesized containing alcohol impurities but nonetheless enabled the synthesis of the salt P9 + [ pfAd ] − . The synthesis of Tl[ pfAd ] in a mixture of H2 O/acetone/ o -DFB demonstrated the water stability of the [ pfAd ] − anion.